The concept of the "eternal left" by Ernst Nolte - Dostanić Dušan (Srpska Politička Misao)
Resume In the article, the author tries to present Ernst Nolte's understanding of the "eternal left". The author starts with the question of whether the concepts of right and left are still usable today. In order to offer an answer to this question, the paper points to the long-established transepochal self-identity of the left. To explain this identity, the author points to the notion of the "eternal left" which was developed within Ernst Nolte's philosophy of history, where the "eternal left" is seen as one of the "historical constants". The text then enumerates the key characteristics of the "eternal left" as understood by Nolte, that is, points out its origin and consequences. Since the fall of communism cannot be considered the final defeat of the "eternal left", the author tries to show that Nolte's understanding is still relevant in our time and that his description of the "eternal left" has not lost its importance.